Ethenesulfonyl Fluoride (ESF) and Its Derivatives in SuFEx Click Chemistry and More - Meng, Yan-Ping; Wang, Shi-Meng; Fang, Wan-Yin; Xie, Zhi-Zhong; Leng, Jing; Alsulami, Hamed; Qin, Hua-Li (Synthesis, 2020)
The sulfur(VI) fluoride exchange reaction (SuFEx), developed by Sharpless and co-workers in 2014, is a new category of click reaction that creates molecular connections with absolute reliability and unprecedented efficiency through a sulfur(VI) hub. Ethenesulfonyl fluoride (ESF), as one of the most important sulfur(VI) hubs, exhibits extraordinary reactivity in SuFEx click chemistry and organic synthesis. This review summarizes the chemical properties and applications of ESF in click chemistry, organic chemistry, materials science, medicinal chemistry and in many other fields related to organic synthesis.1 Introduction2 Chemical Transformations of ESF3 Chemical Transformations of 2-Arylethenesulfonyl Fluorides4 Novel SuFEx Reagents Derived from ESF5 Applications of ESF Derivatives in Medicinal Chemistry6 Applications of ESF Derivatives in Materials Science7 Conclusion
Keywords: sulfur(VI) fluoride exchange; ethenesulfonyl fluoride; 2-arylethenesulfonyl fluorides; sulfur(VI)-based molecules; medicinal chemistry; materials science